2018
DOI: 10.18203/2320-1770.ijrcog20181930
|View full text |Cite
|
Sign up to set email alerts
|

Serum Beta HCG and uterine artery Doppler studies in second trimester to predict preeclampsia and eclampsia

Abstract: Background: Hypertensive disorders during pregnancy remain amongst the most significant and intriguing unsolved problems in obstetrics. The study aims at testing the hypothesis that women with high serum beta hCG levels and alterations in waveforms in the uterine artery doppler in early second trimester have high risk of developing pre-eclampsia.Methods: Serum Beta hCG estimation was done by Sandwich chemiluminescence immunoassay method. All uterine artery waveforms were obtained using a Toshiba nemio ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Like in present study, Mazhari F [3] , Soundararanjan P et al [4] Muthulakshmi D et al [5] , Kulkarni N et al [7] and Rajesh A et al [8] also use hCG production level as a measurement tool for the prediction of pregnancy induced hypertension.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Like in present study, Mazhari F [3] , Soundararanjan P et al [4] Muthulakshmi D et al [5] , Kulkarni N et al [7] and Rajesh A et al [8] also use hCG production level as a measurement tool for the prediction of pregnancy induced hypertension.…”
Section: Discussionmentioning
confidence: 58%
“…In present study, we observed the sensitivity, specificity, positive predictive value and negative predictive value for β-hCG levels for >2MOM were 85.2%, 92.5%, 81.98% and 94.8% respectively. Chowdhary H et al [11] , Pawar P et al [9] , Revankar V M [13] , Soundararajan P et al [4] , Kulkarni N et al [7] , Mazhari F 3 had reported similar findings. In present study, the PIH patients cesarean was done in majority of the cases (77.8%) where as in normotensive patients cesarean was done in 52.0 % and the association was found to be statistically significant between hypertensive and normotensive patients (p< 0.05).…”
Section: Discussionmentioning
confidence: 71%
“…According to this, it was evident that those pregnant women having very high serum beta HCG level >2 MOM and ≥40,000 mIU/ml, the incidence of PIH was more and sensitivity and specificity of β-hCG is 96% and 76% respectively. 6 Rajesh et al also found that β-hCG levels (Mean ± SD) were higher (69808.66±54764.7 vs. 38126.49±97419.2; p<0.28) in subjects who developed gestational hypertension with sensitivity of 75%, specificity of 72.5% and accuracy of 72.8%. 2 Many other authors also have shown significant association between high levels of beta HCG and hypertensive disorders in pregnancy.…”
Section: Resultsmentioning
confidence: 91%
“…[2][3][4] Gestational hypertension along with its sequelae that is preeclampsia and eclampsia can be best described as a human pregnancy-specific syndrome. 5,6 It affect virtually every organ system and widely varies in its clinical phenotypic expression. 6 damage and local hypoxia leading to hemorrhage, necrosis and end organ damage and therefore involves multiple organ systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation